2007
DOI: 10.1017/s0003598x00096046
|View full text |Cite
|
Sign up to set email alerts
|

Waist-to-hip ratios of Jomon figurines

Abstract: The authors show that the Jomon clay figurines made by hunter-gatherers use imagery that emphasises a narrow waist and full hips, showing that a female construct was part of the symbolism of these possibly shamanistic objects. In creating these figurines, prehistoric people were no doubt turning a recognition of health and fertility into more cultural icons. Admirers of the female form will be interested to learn that preference for the fuller, curvaceous ‘hourglass’ shape ‘has probably been the norm over much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The average WHR of the four samples was 0.7 for the female figures and 0.95 for the male figures (Singh 2002a, b). Recently, Hudson and Aoyama (2007) have looked at clay figurines (n=155) from the hunter-gatherer Jomon tradition of Japan (16,500-2,500 BP). Results show that the majority of the figurines had a WHR between 0.65 and 0.69 and less than five figurines from the total sample had a WHR of 0.80 or greater.…”
Section: Cross-generational (Historical) Consensusmentioning
confidence: 99%
“…The average WHR of the four samples was 0.7 for the female figures and 0.95 for the male figures (Singh 2002a, b). Recently, Hudson and Aoyama (2007) have looked at clay figurines (n=155) from the hunter-gatherer Jomon tradition of Japan (16,500-2,500 BP). Results show that the majority of the figurines had a WHR between 0.65 and 0.69 and less than five figurines from the total sample had a WHR of 0.80 or greater.…”
Section: Cross-generational (Historical) Consensusmentioning
confidence: 99%
“…Given that the faces of these 'protruding buttock' figurines are rarely realistically human, it is possible that they represent a mixture of female and 'other', perhaps even mythological, elements. That such a mixture of elements would not necessarily detract from the interpretation put forward here is a point discussed in more detail in Hudson and Aoyama (2007).…”
Section: Interpretation and Discussionmentioning
confidence: 63%
“…This paper is part of a broader project that attempts to examine the representation of physical features on Jomon figurines from prehistoric Japan using evolutionary theory. In previous work we have analyzed the waist-to-hip ratios of these figurines (Hudson and Aoyama, 2007). Here we focus on the buttocks of one type of figurine from Middle Jomon central Honshu and suggest that the exaggerated buttocks of these figurines may be representations of steatopygia.…”
Section: Introductionmentioning
confidence: 99%
“…Singh showed that a low female WHR, such as is judged as highly sexually attractive in many modern populations, was typical of these ancient statuettes. Likewise, Hudson and Aoyama [10] found that Jomon clay figurines made in Japan, made by hunter-gatherers between 16,500-2,500 years ago, typically depict females with low WHRs. These authors conclude that "in creating these figurines, prehistoric people were no doubt turning a recognition of health and fertility into more cultural icons.…”
Section: Introductionmentioning
confidence: 98%